Business and Macroeconomics - Pass Ch. (Christopher); Lowes B.; Robinson A. (London: Routledge, 1995)
"Business and Macroeconomics" offers a concise introduction to macroeconomics, specifically designed to provide students and practitioners of business with an understanding of the workings of the domestic and international economies.
(NP(B/11480s
Keywords: economic growth -- international trade -- investment